Desenvolvimento socioeconômico de Santana do Livramento: uma análise de indicadores - (:unkn) unknown (Universidade Federal do Pampa, 2018)
This monography aims to analyze the socioeconomic development of the town of Santana do Livramento within the period of 2000 and 2016, seeking to understand the changes in socioeconomic development that occurred in this period. The areas of Employment and Income, Health and Education were analyzed, which are responsible for the Firjan Municipal Development Index (IFDM). To analyze the socioeconomic development, data from the IFDM index were used. In addition, secondary information from the municipality and qualitative analysis were used through interviews with the managers of each area. According to the results obtained it is possible to affirm that the year of 2013 was the year with the greatest socioeconomic development through the IFDM, with its index in the value of 0.7130 being considered as a moderate development in the municipality. In order to reach this result, it was possible to observe that Health was the indicator that contributed the most to raise the IFDM of the municipality, showing improvements in its index, mainly in the years 2008, 2009 and 2010 which was considered, according to the IFDM, a development. Another indicator that showed an improvement in its index over the years was Education that ended the period analyzed in the parameter of moderate development. However, the area of Employment and Income was the most deprived, with indices below the others, being in some years as a regular development.
Keywords: Desenvolvimento socioeconômico; Índice Firjan de Desenvolvimento Municipal; Santana do Livramento; Socioeconomic development; IFDM; CNPQ::CIENCIAS SOCIAIS APLICADAS